Beginning Python : from novice to professional - Hetland, Magnus Lie (New York : Apress Media, 2002)
Gain a fundamental understanding of Python's syntax and features with the third edition of Beginning Python, an up-to-date introduction and practical reference. Covering a wide array of Python-related programming topics, including addressing language internals, database integration, network programming, and web services, you'll be guided by sound development principles. Ten accompanying projects will ensure you can get your hands dirty in no time.Updated to reflect the latest in Python programming paradigms and several of the most crucial features found in latest Python 3. Advanced topics such as extending Python and packaging/distributing Python applications, are also covered.
Instant hacking : the basics -- Lists and tuples -- Working with strings -- Dictionaries : when indices won't do -- Conditionals, loops, and some other statements -- Abstraction -- More abstraction -- Exceptions -- Magic methods, properties, and iterators -- Batteries included -- Files and stuff -- Graphical user interfaces -- Database support -- Network programming -- Python and the web -- Testing 1-2-3 -- Extending Python -- Packaging your programs -- Playful programming -- Project 1: Instant markup -- Project 2: Painting a pretty picture -- Project 3: XML for all occasions -- Project 4: In the news -- Project 5: A virtual tea party -- Project 6: Remote editing with CGI -- Project 7: Your own bulletin board -- Project 8: File sharing with XML-RPC -- Project 9: File sharing 2 : now with GUI! -- Project 10: Do-it-yourself arcade game -- Appendix A: The short version -- Appendix B: Python reference.
Includes index.
"User level: beginning-intermediate"--Page 4 of cover.
CSE
Book Finder International
Keywords: Python (Computer program language).; COMPUTERS / Computer Science; COMPUTERS / Programming Languages / Python